Association of Facility and System Factors With Survival Among Pediatric Patients With Surgically Treated Head and Neck Sarcomas - Cheraghlou, Shayan (JAMA Otolaryngol Head Neck Surg, 2018)
This study investigates the role of facility and system factors associated with survival in pediatric patients with head and neck sarcomas.